Contextual Learning with Malay Cultural Content: Developing Social Skills in Preschool Children - Fadillah, Siti; Novitasari, Yesi; Putri, Azlin Atika (Global Education Journal, 2025)
Malay culture-based contextual learning is a meaningful learning experience in supporting children's social development. This study aims to determine the effectiveness of Malay culture-based contextual learning in improving social skills. The method used is a quasi-experimental design with a two-group pretest-posttest control group design. The population of this study were children aged 5-6 years in Rumbai District, Pekanbaru City. The research sample used purposive sampling consisting of 50 children from two institutions, namely Dayyinah Kids Kindergarten and Asri Kindergarten. The results showed that the average value of the experimental class was from 58.44% to 75.80%. Malay culture-based contextual learning in the experimental class was better than the control class without treatment where the average value was 57.88% to 61.12%. The results of the hypothesis test stated that Malay culture-based contextual learning through interactive media had a significant effect on children's social skills, seen from the Sig. (2-tailed) value for the results of the experimental class and control class hypotheses were 0.000 <0.05. Thus, the hypothesis Ho is rejected and Ha is accepted, so it can be concluded that contextual learning based on Malay culture has a positive effect on the social skills of children aged 5-6 years.